2008
DOI: 10.1111/j.1600-0870.2008.00326.x
|View full text |Cite
|
Sign up to set email alerts
|

Scaling of the Atlantic meridional overturning circulation in a global ocean model

Abstract: Using a global ocean model, we revisit the issue of the scaling of the Atlantic Meridional Overturning Circulation (AMOC) versus the vertical diffusivity. With a continuation approach, we are able to compute curves of exact steady solutions of the global model versus the magnitude of the vertical diffusivity KV in the model; we find that the AMOC strength scales as K1/3V. This result is analysed with help of the local density balances in the Atlantic and Pacific. It appears that processes in the Pacific are cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 26 publications
2
14
2
Order By: Relevance
“…In this work, we extend recent process‐oriented studies (Dalan et al, 2005; Dijkstra, 2008) that show that the scaling of the strength of the meridional overturning circulation (MOC) with vertical (or diapycnal) diffusivity ( K V ) is different between the Pacific and Atlantic Oceans. The question of the circulation's sensitivity to K V is rooted in the now long standing thermocline problem (Welander, 1959; Robinson and Stommel, 1959; Welander, 1971).…”
Section: Introductionsupporting
confidence: 51%
See 1 more Smart Citation
“…In this work, we extend recent process‐oriented studies (Dalan et al, 2005; Dijkstra, 2008) that show that the scaling of the strength of the meridional overturning circulation (MOC) with vertical (or diapycnal) diffusivity ( K V ) is different between the Pacific and Atlantic Oceans. The question of the circulation's sensitivity to K V is rooted in the now long standing thermocline problem (Welander, 1959; Robinson and Stommel, 1959; Welander, 1971).…”
Section: Introductionsupporting
confidence: 51%
“…The power law exponent for the Pacific overturning is thus quite close to the classical value of 2/3, but the exponent for Ψ A is clearly smaller. More recently, Dijkstra (2008) analysed the scaling behaviour of the MOC in a fully implicit global ocean‐only model. Using restoring conditions for salinity and a simple energy balance atmospheric model to control upper ocean temperatures, he found that Ψ A scales as K 1/3 V , whereas Ψ P scales as K 2/3 V .…”
Section: Introductionmentioning
confidence: 99%
“…The zonal overturning stream function shows a maximum value of > 4.5 Sv in the basin center at ∼300 m depth. We can compute the formation rate of the intermediate water from the zonal stream function (following Dijkstra [2008], Ezer and Mellor [1997], and Rahmstorf and England [1997]), by considering the volume of the downwelling water east of 25°E. We find that the model predicts a formation rate of ∼2.5 Sv (Figure 7c).…”
Section: General Circulationmentioning
confidence: 96%
“…Forest et al , ; Urban and Keller, ; Olson et al , ), including AMOC strength projections (cf. Dijkstra, ). The results shown in Figure demonstrate that the model hindcasts and projections of AMOC strength are strongly affected by the K v parameter.…”
Section: Resultsmentioning
confidence: 99%
“…Reducing the uncertainty of K v may also result in better predictions of AMOC strength (Dijkstra, ) as well as other climate predictions (Schmittner et al , ). Our main objective is to characterize and (if possible) reduce uncertainty about K v .…”
Section: Introductionmentioning
confidence: 99%